Probing Ligand Exchange in the P450 Enzyme CYP121 from Mycobacterium tuberculosis: Dynamic Equilibrium of the Distal Heme Ligand as a Function of pH and Temperature - Fielding, Andrew J. (J Am Chem Soc, 2017)
CYP121 is a cytochrome P450 enzyme from Mycobacterium tuberculosis that catalyzes the formation of a C–C bond between the aromatic groups of its cyclodityrosine substrate (cYY). The crystal structure of CYP121 in complex with cYY reveals that the solvent-derived ligand remains bound to the ferric ion in the enzyme–substrate complex. Whereas in the generally accepted P450 mechanism, binding of the primary substrate in the active-site triggers the release of the solvent-derived ligand, priming the metal center for reduction and subsequent O(2) binding. Here we employed sodium cyanide to probe the metal–ligand exchange of the enzyme and the enzyme–substrate complex. The cyano adducts were characterized by UV–vis, EPR, and ENDOR spectroscopies and X-ray crystallography. A 100-fold increase in the affinity of cyanide binding to the enzyme–substrate complex over the ligand-free enzyme was observed. The crystal structure of the [CYP121(cYY)CN] ternary complex showed a rearrangement of the substrate in the active-site, when compared to the structure of the binary [CYP121(cYY)] complex. Transient kinetic studies showed that cYY binding resulted in a lower second-order rate constant (k(on (CN))) but a much more stable cyanide adduct with 3 orders of magnitude slower k(off (CN)) rate. A dynamic equilibrium between multiple high- and low-spin species for both the enzyme and enzyme–substrate complex was also observed, which is sensitive to changes in both pH and temperature. Our data reveal the chemical and physical properties of the solvent-derived ligand of the enzyme, which will help to understand the initial steps of the catalytic mechanism.